TEACHER-STUDENTS DISCOURSE IN ENGLISH TEACHING AT HIGH SCHOOL (CLASSROOM DISCOURSE ANALYSIS) - Harahap, Alamsyah; Emzir, Emzir (IJLECR (International Journal of Language Education and Cultural Review), 2015)
English classroom's process of teaching and learning is an important aspect of successful English teaching and learning. The analysis of classroom discourse is a very important form which the classroom process research has taken place. The present study focuses on SMA (high school) English classroom discourse. The microethnography of Spradley was the research method deployed. Through a detailed description and analysis of the collected data referring to Sinclair and Coulthard’s classroom discourse analysis model, the problem of patterns of the classroom discourse is made clear. On the basis of the discourse patterns' problem found, a few strategies for high school English teachers are put forward through the teacher training in order to improve English teaching and learning at high school in Indonesia. The research results showed that teacher talk highly dominated the English classroom discourse; 94% of teacher-students talk. IRF Model of Sinclair and Coulthard was not found in the English classroom (only IF pattern) and no lesson achieved.